(untitled) (Research, Society and Development, 2020)
Objective: to evaluate the strategies used by health professionals in welcoming the nursing mother. Method: this is an integrative literature review, according to the PICO strategy and PRISMA, whose data collection was in the databases BDENF, MEDLINE, LILACS and Virtual Libray SciELO, CAPES Portal. Full articles, available in Portuguese, Spanish and English periodicals, published from 2014 to 2018. Review articles, previous notes and communication between authors were excluded. Results: the research found 1,684 studies from which seven articles that met the inclusion criteria were selected. From the seven articles, five were presented in quantitative synthesis and two, qualitative. It was possible to identify two relevant themes for the discussion: “Different forms of support to the nursing mother by the health professional” and “The nursing mother’s knowledge about breastfeeding and self-efficacy”. Conclusion: the importance of mothers’ learning about breastfeeding techniques and reinforces the need for support and care for breastfeeding women to avoid the early weaning. Therefore, the need for health professionals’ intervention not only to teach the technique and management that involves assertive breastfeeding, but also in actions that reinforce the support focused on the needs pointed out by nursing mothers, is observed.